Perbandingan Pendapatan Usahatani Cabai Rawit Varietas Lokal Dan Varietas Dewata Di Desa Raanan Baru Dua Kecamatan Motoling Barat Kabupaten Minahasa Selatan - Sumangkut, Elsa A.; Kumaat, Ribka Magdalena; Jocom, Sherly Gladys (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the comparison of farming income of local and Dewata varieties of cayenne pepper in Raanan Baru Dua Village, West Motoling District, South Minahasa Regency. This research was conducted in Raanan Baru Dua Village, West Motoling District. Data collection techniques, namely interviews using questionnaires, observation and documentation. The results of this study indicate that the local variety and Dewata variety of cayenne pepper farming in Raanan Baru Dua Village, West Motoling District, South Minahasa Regency, the total production of local varieties of cayenne pepper was 21.662 kg and the total production of cayenne pepper of the dewata variety was 20.214 kg. The average income of local varieties of cayenne pepper farming is IDR 72,803,130 per hectare. While the average income of Dewata variety cayenne pepper is Rp. 66,368,836 per hectare. The results of the T test using the SPSS software application show that there is no significant difference between the farming of the two chili varieties.